Program Unggulan Sekolah Berbasis Islam: Analisis Manajemen Program Tahfiz Qur’an untuk Ketercapaian Target Hafalan - Ismael, Ismael; Muazza, Muazza; Sulistiyo, Urip (Fitrah: Journal of Islamic Education, 2023)
Tahfiz Qur'an is one of the excellent programs that are widely implemented in Islamic-based schools, although it is not specifically mentioned in the national education curriculum. However, sometimes this excellent program is not aligned with the achievement of student memorization. One of the factors is poor management, with regard to that, this study aims to analyze the Qur'an memorization management applied by SMP-IT Ash-Shiddiiqi in achieving the set memorization target. This research uses a qualitative method, based on phenomenology. Data collection used observation, interview and documentation study techniques. The informants were taffiz teachers, school leaders and students. The results revealed that management is evidenced by planning activities which include setting student memorization targets, selecting and training muhafidz/muhafidzoh, selecting students, determining time allocations, creating memorization support programs. Implementation using the itqan method, this model is a method of memorizing the Qur'an by memorizing one by one verse of the Qur'an starting from juz 30. Program evaluation is carried out twice a month, for reporting the muhafidz report every day on the link that has been provided.